Use of organic and inorganic selenium as a supportive therapy in treatment of bovine subclinical mastitis – A study - Sripad, K (Indian Journal of Dairy Science, 2016)
Subclinical mastitis (SCM) is defined as inflammation of udder without any inflammatory changes either in the cow or udder or the milk and hence could be diagnosed by laboratory examination only. Treatment of SCM in dairy cows plays a major role in dairy industry. Researchers have tried combination of antibiotics/antibacterials with or without supportive therapy. Among the supportive therapy adopted in the treatment of SCM, selenium and Vitamin E tops the list. The present study is taken up to compare the efficacy of organic and inorganic selenium with/without Enrofloxacin and Ampicillin–Sulbactam combination, in the treatment of SCM. Twentyfour cows which were positive for SCM, randomly allocated into four treatment groups of six animals each - Group I(control), Group II(Enrofloxacin with Ampicillin-Sulbactam) Group III(Enrofloxacin with Ampicillin-Sulbactam+inorganic selenium) and Group IV (Enrofloxacin with Ampicillin-Sulbactam+organic selenium) were used for the study. Response to treatment using Somatic Cell Count(SCC), was studied up to 105 days. Mean SCC on different days of post treatment within each treatment group revealed significant decrease (P ≤ 0.05) from zero day. When SCC of more than 5 Lakh/ml was considered positive for SCM, it was observed that all the three treatment resulted in mean SCC less than 5 Lakh/ml up to 90th day post treatment. But organic selenium + Enrofloxacin with Ampicillin–Sulbactam reduced mean SCC to the lowest level at 2.03 lakhs/ml. This indicated that oral organic selenium along with Enrofloxacin with Ampicillin–Sulbactam, is more efficacious and beneficial in the treatment of SCM in dairy cows.